2007
DOI: 10.1111/j.1745-7270.2007.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Decreases Plasma Glucose and Improves Insulin Sensitivity in Diabetic Swine

Abstract: To investigate the effects of recombinant human adiponectin on the metabolism of diabetic swine induced by feeding a high-fat/high-sucrose diet (HFSD), diabetic animal models were constructed by feeding swine with HFSD for 6 months. The effects of recombinant adiponectin were assessed by detecting the change of plasma glucose levels by commercially available enzymatic method test kits and evaluating the insulin sensitivity by oral glucose tolerance test (OGTT). About 1.5 g purified recombinant adiponectin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Such a beneficial effect of adiponectin was also observed in db/db obese mice, where adiponectin reversed insulin resistance [142,233]. The same effect was observed in diabetic pigs [234]. Studies on adiponectin and insulin resistance and/or type 2 diabetes have accumulated over the years and all tend towards the conclusion that hypoadiponectinemia is highly associated with the development of those disorders and that it could be considered a risk factor in predicting the occurrence of those disorders in individuals.…”
Section: Insulin Resistance and Type 2 Diabetes Mellitusmentioning
confidence: 75%
“…Such a beneficial effect of adiponectin was also observed in db/db obese mice, where adiponectin reversed insulin resistance [142,233]. The same effect was observed in diabetic pigs [234]. Studies on adiponectin and insulin resistance and/or type 2 diabetes have accumulated over the years and all tend towards the conclusion that hypoadiponectinemia is highly associated with the development of those disorders and that it could be considered a risk factor in predicting the occurrence of those disorders in individuals.…”
Section: Insulin Resistance and Type 2 Diabetes Mellitusmentioning
confidence: 75%
“…Adiponectin suppresses the incorporation of glucose carbon into lipid in primary pig adipocytes (Jacobi et al, 2004). Recently, Hu et al (2007a) determined that administration of recombinant adiponectin to diabetic swine improved insulin sensitivity and enhanced glucose clearance.…”
Section: Influence Of Adipocytes On Other Tissuesmentioning
confidence: 99%
“…As several recent studies have reported, hormones from adipose tissue play an important role in sensitizing the peripheral tissues to insulin (4, 11, 23-25, 51, 58, 64 -66). Adiponectin descreases blood glucose levels and increases insulin sensitivity without increasing insulin levels in diabetic swine (11,24,64), and may well have a role in enabling the mice in the current study to function without a detectable increase in insulin.…”
Section: Discussionmentioning
confidence: 90%
“…high sensitivity to insulin in peripheral tissues. Recent studies show evidence of specific adipokines that enhance insulin sensitivity in the peripheral tissues in the absence of increased levels of insulin (24). Furthermore, considering that the subcutaneous transplants enable a robust recovery of lost adipose tissue, it is likely that adipokines may contribute to the improved glucose homeostasis in addition to insulin in the subcutaneous transplant group.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation